Synthesis and Photocatalytic Activity of BiOCl/Graphene - Qiao, Meiying; Wang, Xuejing (Asian Journal of Chemistry, 2014)
Graphene nanosheets supporting BiOCl catalysts were prepared by hydrothermal method. The structure of BiOCl/graphene was characterized by XRD, SEM, EDS. It’s photocatalytic activity was investigated by the photocatalytic degradation of methyl orange under visible light irradiation. The results shows that the presence of graphene nanosheets could improve the photocatalytic activity of BiOCl under visible light irradiation. The degradation rate of methyl orange reaches 90.91 % when molar ratio of graphene and Bi(NO3)3·5H2O is 15 %.